The myb proto-oncogenes family - Szczylik, Cezary; Pawlak, Wojciech (Contemporary Oncology/Współczesna Onkologia, 1999)
The protooncogene c-myb is a nuclear transcription factor that shares significant sequence homology with two other myb family members, a-myb and b-myb. Myb transcription factors are crucial to the control of proliferation and differentiation in a number of cell types but their mechanism of action is nuclear. The myb family of transcription factors has been strongly implicated in the regulation of cell growth and differentiation in the haematopoietic system. Inhibition of myb function with antisense oligodeoxynucleotides might eventually form the basis for a molecular approach to leukemias therapy.